Anthelminthic Activity of Assassin Bug Venom against the Blood Fluke Schistosoma mansoni - Miray Tonk; Andreas Vilcinskas; Christoph G. Grevelding; Simone Haeberlein (MDPI AG, 2020)
Helminths such as the blood fluke Schistosoma mansoni represent a major global health challenge due to limited availability of drugs. Most anthelminthic drug candidates are derived from plants, whereas insect-derived compounds have received little attention. This includes venom from assassin bugs, which contains numerous bioactive compounds. Here, we investigated whether venom from the European predatory assassin bug Rhynocoris iracundus has antischistosomal activity. Venom concentrations of 10-50 µg/mL inhibited the motility and pairing of S. mansoni adult worms in vitro and their capacity to produce eggs. We used EdU-proliferation assays to measure the effect of venom against parasite stem cells, which are essential for survival and reproduction. We found that venom depleted proliferating stem cells in different tissues of the male parasite, including neoblasts in the parenchyma and gonadal stem cells. Certain insect venoms are known to lyse eukaryotic cells, thus limiting their therapeutic potential. We therefore carried out hemolytic activity assays using porcine red blood cells, revealing that the venom had no significant effect at a concentration of 43 µg/mL. The observed anthelminthic activity and absence of hemolytic side effects suggest that the components of R. iracundus venom should be investigated in more detail as potential antischistosomal leads.